The extraction of lineaments from satellite images in Phayao-fault zone - N. Sukphornsawan (2020)
© Published under licence by IOP Publishing Ltd. Lineament mapping is an important part of structural geological investigation that are important features showing subsurface elements or structural weakness, such as geological faults. Most of lineament features are normally extracted by visual interpretation of enhanced image data. The main objective of this work was to develop a method for semi-automatically extracting lineament using remote sensing data. Landsat 8 OLI original image (excluded band 1, 8, 10 and 11) of Phayao-fault zone was operated. There were three main steps in the study including 1) improve quality of dataset using Principal Component Analysis (PCA), 2) delineate lines from the result of quality improvement and 3) classify lineament using visual interpretation. The results from PCA - Band 3 showed the most correlated when compared with existing data. The extracted lineaments were correlated to geological lineament, stream and road network about 42.46 %, 20.52 % and 7.22 % respectively.